The Efficacy of Low-Iodine Diet Instructional Media for the Preparation of Radioactive Iodine Therapy in Thyroid Patients - Phanachet, Pariya; Lertsomphol, Onanong; Shantavasinkul, Prapimporn Chattranukulchai; Sritara, Chanika (Journal of Health Science and Medical Research, 2023)
Objective: To develop and evaluate a low-iodine diet (LID) instructional media for preparing radioactive iodine (RAI) therapy on LID practices, and knowledge in thyroid patients. Material and Methods: This study was a randomized control trial (RCT), consisting of 120 thyroid participants; divided into 2 groups: a control group (original leaflet) and an intervention group (video and booklets). The efficacy of LID media was determined by measuring iodine intake, urine I/Cr ratio, knowledge tests, satisfaction surveys, and facilitators and barriers during the LID period. Results: This study was conducted with 96 individuals. The energy and biggest nutrient intake changes were significantly lower than the baseline. The iodine intake levels of the intervention group were significantly lower than those of the control group. Conversely, the urine I/Cr ratio and proportion of participants that achieved the criteria of both groups showed no significant difference via inter-group. Participants evaluated “agreed” and “strongly agreed” for satisfaction assessment. Furthermore, both groups suggested the importance of social support and encouragement to attain their goal. Conclusion: The results of the efficacy of LID instructional media were evidence-based for developing and evaluating LID multimedia for preparing RAI therapy in thyroid patients in Thailand. There are also good instruments for advice to thyroid patients in the hospital.